النشاط العسكري في ناحية غرداية من خلال تقارير المنظمة الوطنية للمجاهدين 1956 - 1962 م - نور الهدى كرط; د/ كعبوش بومدين (جامعة عمار ثليجي الاغواط, 2024)
ملخص الدراسة تهدف هذه الدراسة الى التعريف بالنشاط الثوري في ناحية غرداية من خلال ما تضمنته تقارير المنظمة الوطنية للمجاهدين ما بين1956-1962.كما تساهم في ابراز ظروف اندلاع الثورة التحريرية في المنطقة والترتيبات الأخيرة لاندلاع ثورة اول نوفمبر 1954م إضافة الى المعوقات الطبيعية بحكم المنطقة ذات بيئة صحراويةفطبيعة التضاريس وقلة المياه من بين العوائق التي اعترضت الثورة لكن سوف تتبين لنا المقولة القائلة "اهون شيء في الصحراء هو الجند الفرنسي "وذلك من خلال مظاهر الجهد العسكري بالمنطقة المتمثل في العمليات الفدائية التي شارك فيها أبناء الناحية ضد الجيش الفرنسي والخونة والمتعاملين مع سلطة الاحتلال الفرنسي ،بدأت سنة 1956واستمرت الى غاية 1961 ساهمت في نشر الرعب والهلع في صفوف الخونة والقوات الفرنسية. الى جانب ذلك المعارك التي شهدتها الناحية فهي لا تقل عن 18 معركة خاضها عناصر الجيش التحرير الوطنيضد قوات الجيش الفرنسي حيث شملت معظم جهات الناحية، كانت أولها معركة افران في متليلي سنة1957واخرها معركة شعاب لعريق الواقعة يوم 20جانفي1962بمتليلي. الكلمات المفتاحية:الثورةالجزائرية، تقارير، المنظمةالوطنيةللمجاهدين، ناحية غرداية. Study summary This study aims to publicize the revolutionary activity in Gar-daya through the reports of the National Organization of Mu-jahideen between 1956-1962. It also contributes to the condi-tions of the liberation revolution in the region and the recent arrangements for the outbreak of the revolution of November 1954, as well as natural obstacles by virtue of the region, a desert environment. The nature of the terrain and the lack of water are among the obstacles to the revolution, but we will see the saying that "The lowest thing in the Sahara is the French soldier", through the manifestations of the military ef-fort in the area, namely the guerrilla operations in which the people of the region participated against the French army, traitors and dealers with the French occupying Power, which began in 1956 and continued until 1961, contributing to the spread of terror and panic among the French traitors and forces. Besides, the battles in the area are at least 18 battles fought by elements of the National Liberation Army (ELN) against the forces of the French Army, covering most of the fringes, the first being the Battle of Afran in Melili in 1957 and the last being the Battle of Reef of Arq on 20Jan 1962 in Melili. Keywords: Algerian Revolution, Reportsof the National Or-ganization of Mujahideen, Ghardaia